REKONSTRUKSI HUKUM ISLAM: KAJIAN HISTORIS ATAS URGENSI PELEMBAGAAN WAKAF PRODUKTIF DI INDONESIA - Syukron, Ahmad (IAIN Pekalongan, 2011)
This paper studied the urgency of Islamic Law reconception, especially focused on productive wakaf (sustainable Islamic donation) management. As one of Islamic teaching, wakaf has two dimensions, individual and social. If it was worked and managed productively, wakaf would become one of economic power toward Muslims. Following this trend, the study tried to focus on problems of developing productive wakaf management teaching in Indonesia. This study was library research and used historical approach. In gathering data, it took secondary and primary ones, and then analyzed them inductively and deductively, simultaneously